2012
DOI: 10.1111/j.1473-4192.2012.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Not wrong, yet not quite right: Spanish ESL students' use of gerundial and infinitival complementation

Abstract: This study presents a contrastive analysis of gerundial and infinitival complementation produced by Spanish and German ESL learners and English native speakers. An analysis of more than 1,100 attestations of the target constructions obtained from the International Corpus of Learner English reveals that (i) advanced learners' construction choices are not necessarily ungrammatical, yet often non-idiomatic, and (ii) German learners are overall more attuned to native-like choices than Spanish learners. A prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…This may seem perplexing given that specificity is mostly marked by definite and indefinite articles in English, and their L2 acquisition is one of the most notoriously difficult aspects of the English grammar for most learners of English (cf. Master 1997, Butler 2002, Miller 2005. However, the specificity preferences are compatible with, although not completely identical to, another widely-attested constituent ordering preference -given-before-new -and may be recast in terms of difficulty of establishing reference.…”
Section: Commonalities Of Native Language and Interlanguagementioning
confidence: 83%
See 1 more Smart Citation
“…This may seem perplexing given that specificity is mostly marked by definite and indefinite articles in English, and their L2 acquisition is one of the most notoriously difficult aspects of the English grammar for most learners of English (cf. Master 1997, Butler 2002, Miller 2005. However, the specificity preferences are compatible with, although not completely identical to, another widely-attested constituent ordering preference -given-before-new -and may be recast in terms of difficulty of establishing reference.…”
Section: Commonalities Of Native Language and Interlanguagementioning
confidence: 83%
“…In corpus-based SLA research, alternations have generally received only limited attention (for a few exceptions, see Gries & Wulff 2005Callies & Szczesniak 2008;Martinez-Garcia & Wulff 2012). In contrast, as far as native English data are concerned, alternations are among the most intensively researched phenomena.…”
Section: Previous Research On the Genitive Alternation In Nlmentioning
confidence: 95%
“…Supportive evidence comes from Hopp (2013), who found evidence that the anticipatory use of gender information is correlated with the speed of lexical access, in native as well as non-native speakers. In addition, native speakers under time pressure make errors similar to language-learners (Hopp, 2010;McDonald, 2006). A processing deficit account is also directly compatible with a prediction-based approach.…”
Section: Models Of L2 Processingmentioning
confidence: 92%
“…Hopp (Hopp, 2009(Hopp, , 2010 and McDonald (McDonald, 2006), differences between native and non-native speakers can be mainly attributed to resource deficits. Non-native speakers may be slower in accessing lexical items in the L2, or in applying parsing routines that are automatic in native speakers.…”
Section: Models Of L2 Processingmentioning
confidence: 99%
“…For example, Hubbard and Hix () observed that intermediate and even advanced adult learners of English continue to produce verbs in “constructions they do not belong in” (p. 89). That is, except at the very highest levels of proficiency, L2 learners of English are prone to produce certain errors like those in Example 1 that were found online (Bley‐Vroman & Joo, ; Bley‐Vroman & Yoshinaga, ; Hubbard & Hix, ; Inagaki, ; Martinez‐Garcia & Wulff, ; Oh, ).
Example 1a.
…”
Section: Introductionmentioning
confidence: 98%